Impact of Performance Appraisal on Employee Performance: A Critical Case Study of Sui Southern Gas Company Limited - Suleman, Sabera; Cheema , Farooq e Azam (JISR management and social sciences & economics, 2008)
Today, almost in all large/medium-sized organizations, performance appraisal is adopted in one form or the other for administrative purposes, retention/layoff decisions, as well as for developmental purposes. Keeping in view wide-scale efficacy of the performance appraisal as a management tool, the researcher chose Sui Southern Gas Company (SSGC), a public sector autonomous body to study its practical implications. The researcher wanted to determine whether the appraisal program used in the company is merely a useless bureaucratic attempt as part of the company’s requirement. Further, if the company constructively employs appraisal system then this paper addressed the various facets of the performance appraisal exercise and the effect these aspects have on the performance of employees working at SSGC. In-depth interviews and questionnaires were used as main sources of collecting the primary data from the employees of SSGC and the sampling method chosen by the researcher was Stratified Sampling. This study successfully reached the conclusion that although the organization formally focuses on the performance appraisal process, it has not been able to utilize it owing to ineffective evaluation techniques used and a wide communication gap between the managers and the employees in terms of performance management.